Analisis Teknik Permainan Gitar Elektrik Mateus Asato pada Lagu How Deep Is Your Love: Analysis of Mateus Asato's Electric Guitar Playing Technique on the Song How Deep Is Your Love - Farid Yoelhian Nasution; Irdhan Epria Dharma Putra (LPPM ISBI Bandung, 2025)
The purpose of this study is to analyze the electric guitar techniques used by Mateus Asato in his version of How Deep Is Your Love. This research uses a qualitative descriptive method, with the researcher as the primary instrument, supported by tools such as an electric guitar, a laptop, Sibelius software, and YouTube. Data were collected through direct observation of Mateus Asato’s performance videos on YouTube and through document analysis, including scores and video recordings of his interpretation of the song.The results reveal that Mateus Asato uses a variety of distinctive electric guitar techniques, including hybrid picking, slide, bending, vibrato, legato, hammer-on and pull-off, chord melody, palm muting, and artificial harmonics, combined with expressive dynamics and articulation. These techniques contribute to a performance that is emotionally rich and musically nuanced, demonstrating a high level of technical skill and interpretative depth. The findings are expected to serve as a valuable reference for guitarists looking to expand their technical skills and deepen their understanding of artistic expression in song interpretation.